ACTIVATE-2: A Double-Blind Randomized Trial of BCG Vaccination Against COVID-19 in Individuals at Risk - Tsilika, Maria; Taks, Esther; Dolianitis, Konstantinos; Kotsaki, Antigone; Leventogiannis, Konstantinos; Damoulari, Christina; Kostoula, Maria; Paneta, Maria; Adamis, Georgios; Papanikolaou, Ilias; Stamatelopoulos, Kimon; Bolanou, Amalia; et al. (Frontiers in Immunology, 2022)
In a recent study of our group with the acronym ACTIVATE, Bacillus Calmete-Guérin (BCG) vaccination reduced the occurrence of new infections compared to placebo vaccination in the elderly. Most benefit was found for respiratory infections. The ACTIVATE-2 study was launched to assess the efficacy of BCG vaccination against coronavirus disease 2019 (COVID-19). In this multicenter, double-blind trial, 301 volunteers aged 50 years or older were randomized (1:1) to be vaccinated with BCG or placebo. The trial end points were the incidence of COVID-19 and the presence of anti–severe acute respiratory syndrome coronavirus 2 (anti–SARS-CoV-2) antibodies, which were both evaluated through 6 months after study intervention. Results revealed 68% relative reduction of the risk to develop COVID-19, using clinical criteria or/and laboratory diagnosis, in the group of BCG vaccine recipients compared with placebo-vaccinated controls, during a 6-month follow-up (OR 0.32, 95% CI 0.13-0.79). In total, eight patients were in need of hospitalization for COVID-19: six in the placebo group and two in the BCG group. Three months after study intervention, positive anti–SARS-CoV-2 antibodies were noted in 1.3% of volunteers in the placebo group and in 4.7% of participants in BCG-vaccinated group. The ACTIVATE II trial did not meet the primary endpoint of the reduction of the risk for COVID-19 3 months after BCG vaccination; however, the secondary endpoint of the reduction of the risk for COVID-19 6 months after BCG vaccination was met. BCG vaccination may be a promising approach against the COVID-19 pandemic.